Usefulness of training using animal models for colorectal endoscopic submucosal dissection: is experience performing gastric ESD really needed? - Ohata, Ken; Nonaka, Kouichi; Misumi, Yoshitsugu; Tsunashima, Hiromichi; Takita, Maiko; Minato, Yohei; Tashima, Tomoaki; Sakai, Eiji; Muramoto, Takashi; Matsuyama, Yasushi; Hiejima, Yoshimitsu; Matsuhashi, Nobuyuki (Endoscopy International Open, 2016)
Background and study aims: Despite the clinical advantages of colorectal endoscopic submucosal dissection (ESD), an effective training system, especially for Western endoscopists, has been challenging to establish. Herein, we propose a novel training program using ex vivo animal models and evaluate the learning curve of colorectal ESD trainees without gastric ESD experience.Patients and methods: A total of 80 colorectal lesions were prospectively collected and removed by two novice operators. Before human ESD procedures, they received ESD training using an ex vivo porcine “proximal colon” model, which simulates a lumen with many folds and flexions. To assess the validity of our training system, the self-completion and en bloc R0 resection rates, the operation time, and prevalence of complications were compared between the first and latter period. Moreover the factors associated with prolonged operation time were evaluated.Results: The overall rates of self-completion and en bloc R0 resection were 98 % (78/80) and 100 % (80/80), respectively. The operation time during the first period was significantly longer than that during the latter period (86 ± 50 minutes vs. 60 ± 36 minutes, P = 0.01). Regarding complications, only two cases of perforations and delayed hemorrhage were observed during the first period; however, all of the complications were successfully managed endoscopically. The presence of fibrosis was identified as a significant independent predictor of a prolonged operation time during the first period (coefficient, 5.90; 95 %CI, 2.36 – 9.44, P = 0.002).Conclusions: Our trainees achieved high rates of self-completion and R0 resection without severe complications even during the first 20 cases, suggesting that our training programs using ex vivo animal models are useful for trainees without gastric ESD experience.Study registration: UMIN000013566